Modelo de Procesamiento Digital de Señales Cardiacas Desarrollado en MatLab (2013)
The present research aimed to design a model of digital cardiac signal processing developed in MatLab. This is because they wanted to use the potentialities of the computer tool, to emulate a digital processing environment. The design is not experimental, transactional since this model does not directly manipulates the cardiac patient information, but uses the theoretical characteristics of the variable in study. In addition, research is documentary, driven by the precepts of a feasible project, whose methodology consisted of four key stages: characterization of cardiac signal, establishment of the requirements for filtering of cardiac wave, sampling and coding of the signal, and representation of the model in MatLab, as a result, achieved the model of digital processing of cardiac signals using the MatLab tool and corroborating their applicability